Factors affect Vietnamese high school teachers’ intention to quit the teaching profession - Tran, Anh Viet; Tran, Hung Van; Nguyen, Tuong Ngoc Cat; Nguyen, Dat Van (Edelweiss Applied Science and Technology, 2025)
This study investigates five factors influencing teachers’ intention to leave among high school teachers in Ho Chi Minh City, Vietnam: family, salary and benefits, time, colleagues, and superiors. This study uses quantitative methods; data were collected through surveys and analyzed using correlation and regression methods. The study was conducted as a cross-sectional examination of the population of high school teachers in Vietnam. The study’s participants were selected using convenience sampling. The investigation included 324 teachers from middle and high schools in the central districts of Ho Chi Minh City. The survey period was from September to December 2022. The results show that all four factors significantly impact teachers’ intention to leave, with “superiors” being the most influential and “family” having the weakest effect. The study highlights the importance of addressing these factors: “family,” “salary and benefits,” “time,” and “supervisors” to improve teacher retention and create a positive work environment to retain secondary school teachers. Practical implications: The study recommends that policymakers, educational leaders, and school administrators use these findings to implement targeted interventions to improve job satisfaction, work-life balance, and effective leadership practices to retain secondary school teachers and ensure the stability and quality of the education system.